Spin-Based Complementary Logic Device Using Datta-Das Transistors - Koo, Hyun Cheol; Jung, Inhwa; Kim, Chulwoo (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
The spin-FET has been realized using a semiconductor channel, but two complementary transistors analogous to n- and p-type of the conventional charge transistors have not yet been developed. We propose a complementary logic device consisting of two types of devices, namely, parallel and antiparallel spin transistors, in which the alignments of the magnetization directions of the source and the drain electrodes are parallel or antiparallel, respectively. Only one of the two transistors is conducting at a given gate voltage. An assessment of the feasibility was carried out by performing logic gate simulations based on the experimental spin transistor parameters.
Keywords: FIELD-EFFECT TRANSISTOR